1993
DOI: 10.1007/bf00000646
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate limitation of N2O production and denitrification from tropical pasture and rain forest soils

Abstract: Abstract. Nitrous oxide production was measured in intact cores taken from active pasture and old-growth forest Inceptisols in the Atlantic Lowlands of Costa Rica. Following additions of aqueous KNO, or glucose, or the two combined amendments, the cores were incubated in the laboratory to determine if N,O production rates were either N-limited or C-limited in the two land use types. Differences in rates of denitrification (N,O + N, production) among amended forest and pasture soils were determined by addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
3
25
0
1
Order By: Relevance
“…These conclusions are consistent with the interpretation of the field measurements at Nova Vida, which indicated that forest soils did not reach WFPS sufficient to eliminate nitrification and that pasture soils did reach WFPS sufficient to promote denitrification but lacked a sufficient NO − 3 supply to generate comparable emissions of N 2 O and NO. The importance of denitrification at Nova Vida to total N oxide emissions following an increase in the supply of soil inorganic N appeared to be less than those found by other studies of tropical forest (Keller et al 1988;Parsons et al 1993;Verchot et al 1999;Hall and Matson 2003) or pasture (Veldkamp et al 1998). This again appeared to be related primarily to soil moisture status.…”
Section: Relationship Of N 2 O and No Emissions With N Cycling And Somentioning
confidence: 48%
“…These conclusions are consistent with the interpretation of the field measurements at Nova Vida, which indicated that forest soils did not reach WFPS sufficient to eliminate nitrification and that pasture soils did reach WFPS sufficient to promote denitrification but lacked a sufficient NO − 3 supply to generate comparable emissions of N 2 O and NO. The importance of denitrification at Nova Vida to total N oxide emissions following an increase in the supply of soil inorganic N appeared to be less than those found by other studies of tropical forest (Keller et al 1988;Parsons et al 1993;Verchot et al 1999;Hall and Matson 2003) or pasture (Veldkamp et al 1998). This again appeared to be related primarily to soil moisture status.…”
Section: Relationship Of N 2 O and No Emissions With N Cycling And Somentioning
confidence: 48%
“…O menor efeito relativo da adição de dextrose na produção de N 2 O no solo da pastagem-controle, em relação ao Herbicida, é pertinente à resposta da adição de glicose observada em incubações laboratoriais de solos de pastagens da Costa Rica (Parsons et al, 1993).…”
Section: Resultsunclassified
“…On the second level, the clay Oxisol had greater WFPS than the sandy loam Ultisol (Figure 3). Additionally, the response of N 2 O fluxes to increases in WFPS (Parsons et al 1993). Potential denitrification was 4 times greater on the clay Oxisol than on the sandy loam Ultisol .…”
Section: Trace Gas Fluxes In Undisturbed Forestmentioning
confidence: 96%